PERANCANGAN APLIKASI MANAJEMEN PENJUALAN PADA APOTEK ADIBA FARMA - Abd Wahab Syahroni; Nilam Ramadhani (Universitas Islam Balitar, 2021)
The Adiba Farma Pharmacy is a new business place that sells drugs, but wants to have an application in the process of buying and selling transactions at the pharmacy, to make it easier to search drug data, drug location, view drug prices, stocks, drug expiration dates, buying and selling transactions and view reports of sales to consumers and reports of purchases from suppliers. To realize this desire, in this study a pharmacy sales management application is designed that is built using a web-based programming language that can be accessed only on a client server-based pharmacy local computer network. The application is built using the prototype method, the blackbox method is used for application testing. The results of testing with the blackbox method are valid, meaning that 100% of the application's functionality can run well, so it can be said that this application can be used by Adiba Farma Pamekasan pharmacies.